PRINCIPLES OF THE ANTIBACTERIAL THERAPY FOR THE COMMUNITY_ACQUIRED PNEUMONIA AMONG INFANTS - N.A. Korovina; A.L. Zaplatnikov; I.N. Zakharova ("Paediatrician" Publishers LLC, 2007)
The article is dedicated to one of the most urgent issues of the pediatrics - rational antibacterial therapy of the community acquired pneumonia among infants. The authors highlighted the age peculiarities of aetiology and basic criteria for diagnostics, clinical peculiarities and principles of empirical selection of the starting etiotropic therapy for pneumonia among children. They characterized the antibacterial medications allowed for the treatment of pneumonia among children, as well as their regimes of dosage and injection methods.Key words: infants, community acquired pneumonia, diagnostics, treatment, antibacterial therapy.